PENGARUH FASILITAS KANTOR, MOTIVASI KERJA DAN DISIPLIN KERJA TERHADAP KINERJA PERANGKAT DESA DI KECAMATAN BUNTAO’ KABUPATEN TORAJA UTARA - Pangngala, Aditya; Syam, Andi Hendra; M., Andi Syahrul (LPPM University 17 Agustus 1945 Samarinda, 2024)
This study explores how office amenities, work ethic, and occupational discipline affect village apparatus performance indicators in the Buntao' District of the North Toraja Regency. Using a large sample of 45 village officials and an associative quantitative methodology, the study found that the performance of the village apparatus was positively and statistically significantly correlated with office facilities (sig. 0.011 < 0.05), work motivation (sig. 0.018 < 0.05), and work discipline (sig. 0.011 < 0.05). The F-count value of 52.218 exceeded the F-table value of 3.21, indicating that the three independent variables simultaneously showed a positive and significant collective influence. This supports the idea that office facilities, work motivation, and work discipline are important factors influencing the operation of the village apparatus in the aforementioned jurisdiction. Keywords : Office Facilities, Work Motivation, Work Discipline, Performance of Village Apparatus